2016
DOI: 10.1039/c6ra03457h
|View full text |Cite
|
Sign up to set email alerts
|

Effects of aqueous extracts from Ceratonia siliqua L. pods on small intestinal motility in rats and jejunal permeability in mice

Abstract: The current study was performed to assess the effects of carob pod aqueous extracts (CPAE, pulp, seeds or mixture) on gastrointestinal transit (GIT) and intestinal epithelium permeability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
31
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 42 publications
4
31
0
Order By: Relevance
“…This action of intestinal transit facilitation can also be exhibited by the increase effect in intestinal secretion. In this context, similar results were previously published by Rtibi and others () who have shown that the aqueous extract of mature carob pulp causes an increase in intestinal secretion which facilitates the gastrointestinal transit. These findings providing direct evidence that the mature juice of prickly pear fruit exerts a favorable laxative effect.…”
Section: Discussionsupporting
confidence: 89%
“…This action of intestinal transit facilitation can also be exhibited by the increase effect in intestinal secretion. In this context, similar results were previously published by Rtibi and others () who have shown that the aqueous extract of mature carob pulp causes an increase in intestinal secretion which facilitates the gastrointestinal transit. These findings providing direct evidence that the mature juice of prickly pear fruit exerts a favorable laxative effect.…”
Section: Discussionsupporting
confidence: 89%
“…One of these compounds is pyrogallol (1,2,3-trihydroxy benzene). 158 A short summary of these activities can be found in a recent review article that was published by I. C. Theophilou and her colleagues.…”
Section: Discussionmentioning
confidence: 99%
“…102 Carob extracts are being studied in recent years for gastroprotective activities, and they were found highly active, so far. [155][156][157][158][159] Most studies were done in vivo after induction of gastric disorder in animals. These diorders were induced by various chemicals such as ethanol, hydrochloric acid, sodium chloride or dextran sulfate sodium.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…siliqua pods are used in various regions of the world including Pakistan for the treatment of diarrhea and constipation by traditional medicine practitioner. Recently a scientific in vivo study was conducted on immature and mature carob pods which claimed that phytochemical constituent(s) variations in immature and mature carob pods play a role in the management of diarrhea and constipation (Rtibi et al, 2016b).…”
Section: Discussionmentioning
confidence: 99%